Samotherium boissieri from the Late Miocene of Southern Italy - Antonella Cinzia Marra (Life, 2025)
Samotherium boissieri is a giraffid typical of the Pikermian biome, well documented at Samos and occurring in the late Miocene of the Greco-Iranian paleobioprovince. The species has been also recorded at Cessaniti in Calabria (Southern Italy), in a faunal association including other Pikermian species as well as species of Eurasian and African affinity. In this paper, Calabrian specimens are studied and compared to Samos ones. Morphological and biometrical data fall within the variability of Samotherium boissieri and clearly differ from the co-occurring giraffid, Bohlinia attica. Two partially complete forelimbs, probably referring to the same individual, permit the first full description of the manus bones for the species, carpals in particular. The occurrence of Samotherium boissieri in Calabria contributes to the wide discussion on paleobiogeographical assessments of the central Mediterranean in the late Miocene, still not well-understood.